1991
DOI: 10.1007/bf00171032
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with Pilogel/β-blocker in glaucoma patients

Abstract: In a multicentre clinical trial thirteen patients with primary open angle glaucoma or ocular hypertension were followed during at least six months while selfinstilling Pilogel (once daily) and topical beta-blocker (twice daily). After six months of combination therapy there was an average decrease in intra-ocular pressure (IOP) of 33.6% 9.5 hours after Pilogel administration and an IOP decrease of 23.4% 22.5 hours after Pilogel administration. With topical beta-blocker alone, an average IOP decrease of 15% was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…1), fine and coarse punctate epithelial keratitis, areolar punctate keratitis, and filamentary keratitis. Early studies estimated a prevalence of 44-46% of SPK in glaucoma patients on pilocarpine [7,8]. Early studies estimated a prevalence of 44-46% of SPK in glaucoma patients on pilocarpine [7,8].…”
Section: Superficial Punctate Keratitismentioning
confidence: 99%
See 1 more Smart Citation
“…1), fine and coarse punctate epithelial keratitis, areolar punctate keratitis, and filamentary keratitis. Early studies estimated a prevalence of 44-46% of SPK in glaucoma patients on pilocarpine [7,8]. Early studies estimated a prevalence of 44-46% of SPK in glaucoma patients on pilocarpine [7,8].…”
Section: Superficial Punctate Keratitismentioning
confidence: 99%
“…More recently, a hyperosmolar environment was found to potentiate the cytotoxicity of BAK in conjunctival cells, consistent with its independent role in ocular surface inflammation in DES [34 & ]. 8 4000 patients found preservative-free formulations had reduced subjective complaints of irritation and discomfort upon and between instillations, and decreased frequencies of abnormal slit-lamp findings such as hyperemia, follicles, SPK, and palpebral signs [12]. 8 4000 patients found preservative-free formulations had reduced subjective complaints of irritation and discomfort upon and between instillations, and decreased frequencies of abnormal slit-lamp findings such as hyperemia, follicles, SPK, and palpebral signs [12].…”
Section: Studies On Corneal and Conjunctival Epitheliummentioning
confidence: 99%
“…Previous studies have reported tear instability and reduced tear quantity in over 60% of glaucoma patients. The rate of punctate corneal erosions can be as high as 18–54% in patients receiving antiglaucoma eye drops [ 17 , 18 , 19 , 20 , 21 , 22 ]. On the severe end of the ocular surface disease (OSD) spectrum is pseudo-pemphigoid, which can be diagnosed in up to 28.3% of chronic eye drop users [ 23 ].…”
Section: Discussionmentioning
confidence: 99%